Hip fractures in patients with inflammatory bowel disease and their relationship to corticosteroid use: a population based cohort study. Issue 2 (14th January 2004) - Card, T; West, J; Hubbard, R; Logan, R F A
Abstract : Background: Inflammatory bowel disease (IBD) is known to be associated with reduced bone density but the extent to which this results in an increased risk of fracture and the contribution of corticosteroid therapy are unclear. We have conducted a large cohort study to address these issues. Methods: We selected subjects within the General Practice Research Database (GPRD) with a diagnosis of IBD and up to five matched controls for each patient. We derived dates of recorded hip fractures and also information on smoking, use of corticosteroids, and a number of other drugs. We calculated the absolute risk of fracture and the relative risk as a hazard ratio corrected for available confounders by Cox regression. Results: Seventy two hip fractures were recorded in 16 550 IBD cases and 223 in 82 917 controls. Cox modelling gave an unadjusted relative risk of hip fracture of 1.62 (95% confidence interval (CI) 1.24–2.11) for all IBD, 1.49 (1.04–2.15) for ulcerative colitis (UC) and 2.08 (1.36–3.18) for Crohn's disease (CD). Multivariate modelling showed that both current and cumulative use of corticosteroids and use of opioid analgesics confounded this relationship. After adjusting for confounding, the relative risk was 1.41 (0.94–2.11) for UC and 1.68 (1.01–2.78) for CD. Conclusion: The risk of hip fracture is increased approximately 60% in IBD patients. Corticosteroid use is a contributor to this, both in the long term as previously recognised and also in an acute reversible manner. The majority of hip fracture risk in IBD patients however cannot be attributed to steroid use.